Pectinolytic activity secreted by yeasts isolated from fermented citrus molasses - Oliveira, K. F.; Malavolta, L.; Souza, C. S.; Vicente, E. J.; Laluce, Cecília [UNESP] (Blackwell Publishing, 2006)
Aims: the aim of this study was to obtain improved strains of pectinolytic yeasts adapted to the conditions of an industrial fermentation process, which was continuously operated to convert citrus molasses into ethanol.Methods and Results: the starter yeast of the industrial fermentation process was a commercial baker's yeast, which was capable of growing without forming any secretion halo of pectinase activity on solid medium. Nevertheless, isolates showing secretion of pectinolytic activity on plates were obtained from the fermentation process. The secretion of pectin-degrading activity by isolates on plates was repressed by galactose and improved as the result of colony aging on polygalacturonic acid plates at 30 degrees C. Liquefaction of polygalacturonate gels as well as the splitting of the pectin-degrading activity into a wall-linked and a supernatant fraction were also observed when the starter yeast was propagated under agitation in liquid medium containing pectin.Conclusions: Isolates capable of secreting pectinolytic activity on plates were predominant at the end of the citrus molasses fermentation. Nevertheless, the sizes of the secretion haloes on plates were not necessarily an indication of the levels of pectinolytic activity secreted in the liquid medium.Significance and Impact of the Study: Improved pectinolytic strains of Saccharomyces can be used as a source of pectinases for a variety of applications. This organism also participates in plant deterioration processes.
Keywords: colony aging; pectinase; pectinolytic yeasts; polygalacturonase; Saccharomyces; wall-linked pectinase activity